Correction to “A Career in Catalysis: Daniel Resasco” - Joaquin Resasco; Jimmy Faria Albanese; Walter E. Alvarez; Steven Crossley; Gary L. Haller; José E. Herrera; Gary Jacobs; Johannes A. Lercher; Gengnan Li; Lance L. Lobban; Fabio Bellot Noronha; M. Pilar Ruiz; et al. (ACS Catalysis, 2026)
In the original manuscript, José E. Herrera was inadvertently omitted from the author list. He contributed to the section on carbon nanotubes. The author list has been corrected to reflect his contribution.
Keywords: Catalysis and Oxidation Reactions; Zeolite Catalysis and Synthesis; Asymmetric Hydrogenation and Catalysis